Critical Lens in Learning Analytics Research: A Systematic Literature Review - Moraes, Marcia Cristina; Folkestad, James E.; Birmingham, Daniel (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
This paper describes a systematic literature review that aims to answer the following research question: How has critical theory been used in learning analytics research? Nine previous literature review and fifteen studies were analyzed. Results showed that none of the previous literature reviews considered critical theory as a component of their analyzes and the topics of algorithm bias, ethics, justice and prediction are among the most studied on works that used Critical lens in Learning Analytics. Considerations are drawn to support future works that promotes the use of Critical lens in Learning Analytics and in the design of adaptive systems for learning and teaching.